Nature-reserve fund Kiverzivsky district of Volyn region - Музиченко, О. С.; Веселуха, Т. В. (Man and Environment. Issues of Neoecology, 1970)
One of the strategic tasks of the state environmental policy of Ukraine for the period up to 2020 is to increase the area of the national econet, which should take place by expanding existing and creating new objects of the nature reserve fund, which is legally approved by laws and national programs in the field of development of the ecological network And a reserved case. Purpose. The study of the structure and spatial distribution of protected areas and objects Кiverzivsky district of Volyn region, determining quality of nature reserve network. Methods. Comparative geography, mathematics, graphing, statistical, analytical. Results. The structure and spatial distribution of protected areas and sites of the area. The quality of the protected areas and territories assessed for coefficient of nature protection and insularization, an indicator of density, uniformity of distribution. Established landscape and geographical representation network of protected areas. The structure of reserved area is characterized by uneven distribution. Dominated facilities of less than 50 hectares, their portion of the total number is 70,59%. High іnsularization (0,36) points to significant fragmentation of protected areas and their area of environmental instability. Directions improving territorial structure protected area network. Conclusions. For the further successful development of the conservation area on the territory, the next step should be the completion of the development of schemes for the formation of the ecological network of natural nuclei and ecocorridors of national importance in order to ensure the possibility of natural migration and distribution of plant and animal species, preservation of valuable natural elements of the environment. Important role in ensuring reliable migratory biotic connections is given to the NPC "Tsumanska Pushcha".